Concrete microstructure, properties, and materials - Mehta, P.K. (Povindar K.); Monteiro, Paulo J.M (McGraw-Hill, 2006)
Presents the art and science of concrete in a hands-on manner. It predicts cement and concrete to be the premier building material of the 21st Century. It includes diagrams, photographs, and summary tables. It includes chapters on non-destructive methods for concrete, challenges in concrete technology and examples of concrete applications.